La motivación y su incidencia en el proceso de aprendizaje de los estudiantes de la Unidad Educativa Emigdio Esparza Moreno de cuarto año de educación básica - Moran Leon, Kelly Dayana (2025)
The present research work will deal with Motivation and its incidence, determining the degree of motivation in the learning process of students in the fourth year of general basic education made up of 34 students legally enrolled and 1 teacher of the Emigdio Esparza Moreno Educational Unit of the city of Babahoyo, parish of Clemente Baquerizo, focusing on the lack of motivation that exists in the classroom, noting that the teacher of this educational unit works with empathy and charisma, prioritizing meaningful learning. Even new learning techniques are investigated to help in the motivation of students inside and outside the educational establishment. In order to implement this research work, the qualitative methodology will be used to identify each problem found through the survey, being applied to both the students and the teacher, taking into account that the teacher uses motivation in their daily classes so that students better grasp their ideas and teachings. According to the research carried out by (Armstrong, 1991), he maintains that the stimulation or motivation of human resources is based mainly on preserving the values of the group that culturally advance to a superior performance. According to (Collective of Authors 2004) the teaching-learning process has as its definition the mobilization of students taking guidelines from the teacher, to achieve knowledge, habits, skills to form a scientific base. Taking into consideration that the study is logically related to the teacher and students, the tutor-teacher must motivate, incite, examine the learning of the students so that they are able to participate and grasp the activities.